Hubungan Pendekatan Social Emotional Learning (SEL) dengan Karakter Disiplin pada Kelas 3 di SDN 8 Telaga Biru - Salsabila R. Solang; Winda Lalu; Nayla Faradilla; Nabila Nabila; Iyutri Ladiku; Lila Anggraini Ponongoa (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aimed to examine the implementation of the Social Emotional Learning (SEL) approach in developing disciplined and polite character among third-grade students at SDN 8 Telaga Biru. The research used a quantitative method with a correlational approach. The variables in this study consisted of the SEL approach as the independent variable (X) and student’ disciplined and polite character as the dependent variable (Y). Data were collected through observation, questionnaires, and documentation. The collected data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test.The results showed that the implementation of the SEL approach at SDN 8 Telaga Biru was categorized as good, with a percentage of 72.00%. The disciplined and polite character of students was also categorized as good, with a percentage of 80.00%. The correlation test result obtained a coefficient value of r = 0.40, indicating a moderate positive relationship between the SEL approach and students’ character development. The learning environment plays a critical supporting role in this relationship, as a safe, inclusive, and emotionally supportive classroom setting amplifies the effectiveness of SEL implementation.Therefore, it can be concluded that the SEL approach positively correlates with the formation of disciplined and polite character in elementary school students. A well-structured and conducive learning environment is essential to optimize the outcomes of SEL-based character education.